The Effect of Prudence, Financial Distress and Litigation Risk on Audit Quality Moderated by the Characteristics of the Audit Committee Chairman - Whittleliang Hakki, Tandry; Loanza, Marshia; Wong, Natasya (DINASTI RESEARCH, 2025)
This study aims to examine the influence of Prudence, Financial Distress, and Audit Quality on Audit Quality and to explain the role of the audit committee chairman as a moderator of the influence of Prudence, Financial Distress, and Audit Quality on Audit Quality. The type of data used in this study is primary data in the form of financial reports of companies used as samples. The research method used in this study is a quantitative research method. The sample was selected using a purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the expected research results in this study are Prudence influences audit quality, Financial Distress with the Springate method influences audit quality, Financial Distress with the Zmijewski method influences audit quality, Litigation Risk influences audit quality, The characteristics of the Audit Committee Chairman strengthen the influence of Prudence on audit quality, The characteristics of the Audit Committee Chairman strengthen the influence of Financial Distress with the Springate method on audit quality. The characteristics of the Audit Committee Chairman strengthen the influence of Financial Distress with the Zmijewski method on audit quality. The characteristics of the Audit Committee Chairman strengthen the influence of Litigation Risk on audit quality.